Järjestäytyminen ja yhteiskunnan muutos : järjestötoiminnan alkuvaiheet ja laajentuminen suomenkielisellä Etelä-Pohjanmaalla vuoteen 1908 - Latikka, Olavi (1987)
In the last decades of the period of autonomy (1809-1917), the great social turning point occurred in Finland as a side effect of industrialization. People have recently been interested in, among other things, the effect of organizations on that change. This study tries to shed light on the development mainly from the point of view of one single province – Finnish-speaking Ostrobothnia - where organizational activities of all kinds started very early. In this area, Fennomania, Finnish nationalism against the ruling Swedish-speaking minority, had a cultural political tendency, and represented a kind of social radicalism. The parish of Ilmajoki with its surroundings was clearly the centre of economic and ideal organizational activities towards the end of the 1800's. But after the turn of the century, there was a gradual change in the emphasis of the activity. In the parishes of the river Lapua, and especially in Lapua, a very strong passive opposition came into being during· the so called years of oppression (1899-1905). In all organizational activities there was also an especially large increase in memberships. In connection with this change, provincial influence begun to go over in the direction of Lapua. But after the turn of the century, there was a vigorous growth in activities and memberships all over Finland. At the same time, southern Ostrobothnian organizational activities lost the pioneering position and took on a defensive character. One reason for this change of character was a type of relative poverty in the province. However, in the national integrational sense, southern Ostrobothnia became the so called periphery, which didn't yield much to the will of the central districts of the state. Finnish nationalism was acknowledged by the leading peasants in the 1870's, and in the 1880's social radicalism arose within it in some places. The most essential goal of the youth association movement (1881-) was self-education and the defending of rural values. From here it was not a long way to a new party, a southern Ostrobothnian branch of the Agrarian Party. Both movements and especially the Agrarian Party's (1906-) world of ideas consisted of elements of the old and new society. They affected the conflict between the centre and periphery. Without the Agrarian Party's social cautiousness the clashes between the old · and the new society might have been even more powerful in southern Ostrobothnia.